1964
DOI: 10.1126/science.145.3628.156
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Expansion in Aging Women: Implications for Osteoporosis and Fractures

Abstract: In femoral radiographs of 2030 aging women, the diameter of the midshaft periosteum increased as cortical thickness declined. Since the cortical area enlarged, periosteal accretion exceeded endosteal resorption. Since the section modulus increased more than did cortical area, the ratio of flexural failure resistance to crush resistance increased, in apparent contrast to the changes observed in the femoral neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
129
1
2

Year Published

1972
1972
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(144 citation statements)
references
References 3 publications
12
129
1
2
Order By: Relevance
“…Periosteal expansion occurs throughout life. The rate of expansion is high during puberty, 17 slower during the adult years 106,117 and in women, accelerated again after menopause. 1 Independently of other changes, expansion of the periosteal surface increases the strength of long bones and decreases the risk of fracture.…”
Section: Microscopic Featuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Periosteal expansion occurs throughout life. The rate of expansion is high during puberty, 17 slower during the adult years 106,117 and in women, accelerated again after menopause. 1 Independently of other changes, expansion of the periosteal surface increases the strength of long bones and decreases the risk of fracture.…”
Section: Microscopic Featuresmentioning
confidence: 98%
“…These cells likely do serve to expand the periosteal diameter, as the femoral neck experiences age-associated radial expansion. 11,106,117 It may be, however, that limited quantity of cells limits the rate of expansion, resulting in less than optimal bone geometry and therefore elevated fracture risk. Alternatively, these data may present supporting evidence that the femoral neck exhibits an alternative means of periosteal apposition.…”
Section: Microscopic Featuresmentioning
confidence: 99%
“…The present study, with a larger sample of femoral necks, is consistent with their findings. The periosteum plays a vital role in bone formation and radial bone expansion with age (Smith & Walker, 1964). A recent investigation by Benjamin et al (2000) observed ossification of the calcified fibrocartilage zone of the Achilles tendon in young rats.…”
Section: mentioning
confidence: 99%
“…Various reports have supported the role of periosteal apposition as a mechanism to preserve bone strength in the context of agerelated trabecular and cortical bone loss [1,3,7,9,12,19,30,31,33,36,37]. However, none of these reports have focused on examining age-related material and geometric changes in the trochanter and comparing these changes to those observed in the femoral neck.…”
Section: Introductionmentioning
confidence: 99%